A survey on Cryptosporidium spp. infection in lambs with and without clinical signs of diarrhea in Jovein area - Robabe keyvanloo Shahrestanakey; Alireza Taghavi razavizadeh; Gholamreza Razmi (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2017)
Cryptosporidium parvum is an enteric pathogen of a broad range of animals including ruminants. It is also important in terms of public health due to its transmission from animals to humans. The purpose of the present study was to determine the infection rate of this parasite in lambs raised in farms of Jovein area as a center of sheep production in khorasan-razavi province. At first, some sheep flocks were selected randomly, then fecal samples were collected from the rectum of 300 lambs with the age of 10 days to two months during four seasons between summer 1393 to spring 1394 (July 2014 to May 2015). After recording the sampling time, age, sex, and presence or absence of clinical signs of diarrhea in studied lambs, the samples were transported to the parasitology laboratory. Smears were prepared and stained by modified Ziehl-Neelsen method and examined by light microscopy using magnification of 100× (oil immersion). The results of 150 cases of diarrheic and 150 cases of non- diarrheic stools showed that the infection rate is 3% (9 positive samples). Two (1.3%) and 7 (4.6%) positive samples belonged to diarrheic and non- diarrheic lambs, respectively. The Chi-square test revealed no statistically significant correlation between the protozoan infection rate with diarrhea, age, sex and season of sampling. Although the cryptosporidium infection rate in lambs were relatively low in Jovein area, but sheep should not be overlooked as a possible source of infection that could threaten public health.